1973
DOI: 10.1037/h0034714
|View full text |Cite
|
Sign up to set email alerts
|

Training interviewers to eliminate contrast effects in employment interviews.

Abstract: Contrast effects have been found to be a potentially serious source of error in interviewers' ratings of job applicants. A series of experiments was conducted in an attempt to eliminate these errors. Use of a warning in the first experiment was not successful. Use of an anchoring treatment in the second experiment was equally unsuccessful. Combining and strengthening the warning and anchor treatments in the. third experiment also failed, revealing that contrast effects are a surprisingly tenacious source of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 4 publications
3
64
2
1
Order By: Relevance
“…This is in keeping with what has been reported as constituting good training: instruction, coaching and supervised practice (Schuh, 1981). Edwards' review of the psychology and business interview literature (Wexley et al, 1973;Latham et al, 1975;Keenan, 1978) promoted the conclusion that training interviewers can improve performance in interviewing.…”
Section: Measurement Propertiessupporting
confidence: 62%
“…This is in keeping with what has been reported as constituting good training: instruction, coaching and supervised practice (Schuh, 1981). Edwards' review of the psychology and business interview literature (Wexley et al, 1973;Latham et al, 1975;Keenan, 1978) promoted the conclusion that training interviewers can improve performance in interviewing.…”
Section: Measurement Propertiessupporting
confidence: 62%
“…Wexley et al (1973), in their study of interviewer decision behaviors, found that it was very difficult to reduce some rating errors. An interviewer training program stressing basic principles of learning was the most effective vehicle.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Wexley, Sanders, & Yukl (1973) used a two-hour session to train undergraduate interviewers to be less susceptible to contrast rating errors. Pulakos (1984) employed one-and-one-half-hours of training of undergraduates in order to reduce various rating errors that frequently occur when evaluating employees.…”
Section: Methodsmentioning
confidence: 99%
“…A second alternative explanation for the inconsistency penalty is perceptual contrast (e.g., Herr, 1986;Murphy, Balzer, Lockhart, & Eisenman, 1985;Sherif & Hovland, 1961;Wexley, Sanders, & Yukel, 1973). An individual's transgressions may seem worse when contrasted against any relevant values, even those espoused by an organization to which the individual does not belong.…”
Section: Robustness Checksmentioning
confidence: 98%